Estação Carandiru e o mundo construído pelas formas de nomeação - Maria Aparecida Silva Ribeiro (Estudos de Literatura Brasileira Contemporânea)
In the context of the emergence of literary narratives about prison and violence, observed in late 1990s, Estação Carandiru, by Drauzio Varella, is published. Joined by the set of texts whose authors are mostly beginners and which comprises also Cidade de Deus by Paulo Lins, Pavilhão Nove by Hosmany Ramos and Capão Pecado by Ferréz, among others, the novel presents a urban reality, contemporary, realistic and violent according to the common sense that guided their reports. These stories, before assuming novelistic format, had circulated only as journalistic fact, several of them having been subsequently adapted for the cinema. This article proposes a reading of the text of Varella, from the choices practiced in their nomination process, which subsidize the narration, in line with traditional of the narrator setting enunciated by the philosopher Walter Benjamin. It also scrutinizes the ways in which space, almost a character in the story told, is built by nominating speech, in its excesses and shortages.